(untitled) (International Journal of Advanced Research in Computer Science, 2017)
The basic problem is to identify the alternative means of achieving a given objective and then to select the alternative that accomplishes the objective in the most efficient manner, subject to constraints on the means which is referred as an optimization. In this paper a brief study of different optimization techniques along with their classification, used for digital filter design and analysis are reviewed along with Integer linear Programming algorithm which provides effective results in constraint with time. Â Keywords: Optimization, Simulated Annealing (SA), Particle Swarm Optimization (PSO)